The Criminal Liability for Human Actions Involving Stem Cells in Jordan: A Comparative Law Study - Ahmad Al-Shawabkeh, Barjes Khalil (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study clarified the criminal liability for the disposal of human stem cells according to Jordanian legislation compared to Indonesian legislation, depending on the type of this disposal, whether by way of sale or by way of donation. Hence, the researcher followed the descriptive and analytical approach to present the texts criminalizing the disposal of stem cells and analyze their content to determine the scope and limits of criminal liability for this disposal to prevent the misuse of stem cells for material gain. The study revealed a set of conclusions, which consisted of criminalizing the disposal of stem cells in exchange for financial compensation and permitting such disposal if it is by way of donation, with the possibility for the donor to receive simple compensation that does not rise to the level of the financial compensation for these cells, provided that informed consent to the donation is given. The transfer of stem cells to another body does not harm public health. The Jordanian legislature recommends that some amendments be made to the elements criminalizing the disposal of stem cells, depending on the degree of risk it poses to the mere sale or trafficking, as reflected in the number of penalties prescribed for each criminal case in a manner commensurate with the criminal gravity.